+0  
 
0
261
1
avatar

x=2y and x^2+2x-y-y^2=36

Guest Dec 7, 2017

Best Answer 

 #1
avatar+27044 
+1

x=2y  (1)

x^2+2x-y-y^2=36 (2)

 

Replace x in (2) by 2y

 

4y^2 +4y -y - y^2 = 36

3y^2 + 3y = 36

y^2 + y = 12 

y^2 + y - 12 = 0

(y + 4)(y - 3) = 0

 

Hence (i) y = -4, and using (1) x = 2*(-4) or x = -8

and     (ii) y = 3, and using (1) x = 2*3 or x = 6

Alan  Dec 7, 2017
 #1
avatar+27044 
+1
Best Answer

x=2y  (1)

x^2+2x-y-y^2=36 (2)

 

Replace x in (2) by 2y

 

4y^2 +4y -y - y^2 = 36

3y^2 + 3y = 36

y^2 + y = 12 

y^2 + y - 12 = 0

(y + 4)(y - 3) = 0

 

Hence (i) y = -4, and using (1) x = 2*(-4) or x = -8

and     (ii) y = 3, and using (1) x = 2*3 or x = 6

Alan  Dec 7, 2017

10 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.